1993
DOI: 10.3382/ps.0721873
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 5-Fluorouracil Treatment of Chicks: A Cell Depletion Model for the Study of Avian Polymorphonuclear Leukocytes and Natural Host Defenses

Abstract: Two-week-old Leghorn chicks injected intravenously with 5-fluorouracil (5-FU) were found to have a three- to fivefold reduction (P < .05) in circulating polymorphonuclear leukocytes (PMN) 5 to 10 days later. The reduction in PMN was dose-dependent with a dosage of 200 mg/kg body weight of 5-FU, causing suppression of PMN to almost undetectable levels. Increasing the dosage of 5-FU to 400 mg/kg had no further effect on reducing the number of PMN in the circulation nor were overt clinical signs of toxicity obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…However, the number of heterophil granulocytes was drastically reduced in both treated groups 7 and 8 days after 5-FU treatment, 2 and 3 days after virus inoculation, when viraemia was expected. The results of the blood cell counts were too few to be statistically evaluated, but the effect of 5-FU on blood cells seemed already discussed in detail by Kogut et al (1993) and Bojesen et al (2004). The histological studies of bursa tissues confirmed the results of lymphocyte counts, revealing cellular depletion 5 days after 5-FU treatment.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…However, the number of heterophil granulocytes was drastically reduced in both treated groups 7 and 8 days after 5-FU treatment, 2 and 3 days after virus inoculation, when viraemia was expected. The results of the blood cell counts were too few to be statistically evaluated, but the effect of 5-FU on blood cells seemed already discussed in detail by Kogut et al (1993) and Bojesen et al (2004). The histological studies of bursa tissues confirmed the results of lymphocyte counts, revealing cellular depletion 5 days after 5-FU treatment.…”
Section: Discussionsupporting
confidence: 56%
“…The effect of 5-FU is related to its replacement of uracil in RNA (Ardalan & Glazer, 1981). A dose of 200 mg/kg was injected once into the vena ulnaris (Kogut et al ., 1993). Sterile saline was used as placebo.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another result underlining the importance of chicken heterophils in protection against Salmonella organ invasion was the finding that intraperitoneal administration of S. Enteritidis-immune lymphokines (SE-ILK) to 18-week old chickens protected the animals from organ invasion by S. Enteritidis (Hargis et al, 1999;Tellez et al, 1993). SE-ILK are soluble products produced by Tlymphocytes, derived from S. Enteritidis-immune hens, cultured in the presence of concanavalin A. Intraperitoneal administration of SE-ILK in chickens resulted in a dramatic increase in the number of heterophilic granulocytes into the peritoneum without changing the numbers of other leukocytes and administration in ovo protected young chicks against organ invasion by Salmonella (Kogut et al, 1995a(Kogut et al, , 1995b.…”
Section: Immunity To Salmonellamentioning
confidence: 99%
“…Granulocytopoenic (heterophil-depleted) chickens are much more susceptible to S. Enteritidis organ invasion, with the increase in bacterial number in the internal organs being proportionally related to the decrease in number of circulating PMNs (Kogut et al, 1993;Ibid 1994). Another result underlining the importance of chicken heterophils in protection against Salmonella organ invasion was the finding that intraperitoneal administration of S. Enteritidis-immune lymphokines (SE-ILK) to 18-week old chickens protected the animals from organ invasion by S. Enteritidis (Hargis et al, 1999;Tellez et al, 1993).…”
Section: Immunity To Salmonellamentioning
confidence: 99%